Implementasi Metode Convolutional Neural Network Untuk Identifikasi Pola Aksara Batak - Tumiar Butar - Butar; Berto Nadeak; Imam Saputra (Forum Kerja Sama Penddikan Tinggi (FKPT), 2022)
The pattern of the Batak script is the writings of the Batak language which is an important part in the introduction of the Batak script. The Batak script consists of five major dialects, namely Angkola-Mandailing, Karo, Pakpak-Dairi, Simalungun, and Toba dialects. The writings in the Batak script, especially the Toba Batak script, are of course very difficult to understand and study by the current millennial generation. This is due to the lack of people who are experts in the field of Batak script to teach about the Batak script, especially the Toba Batak script. Convolutional neural network (CNN) is part of an artificial neural network that is used as a place to process data in two-dimensional form (multi-layer perceptron), namely sound and images or in other words as a form of pattern recognition. Convolutional neural network (CNN) is used in Batak script patterns as a tool for pattern recognition that will help recognize Batak script patterns into computer form using MatLab so that it is more effective and efficient to learn. Thus, the use of the Convolutional neural network (CNN) method in the Batak script will again bring up a sense of curiosity to learn the Batak script, especially the Toba Batak script. And also with the Convolutional Neural Network (CNN) method in Batak script, it will make the identification process easier.